PRODUKSI DAN KARAKTERISASI ECO-ENZIM DARI LIMBAH ORGANIK DAPUR - Widiani, Nurhaida; Novitasari, Aulia (BIOEDUKASI (Jurnal Pendidikan Biologi), 2023)
Garbage is the main problem causing environmental problems which are dominated by organic waste. Management of organic waste must be carried out extensively, one of which is by making eco-enzymes. This study aimed to determine the production of eco-enzymes from kitchen organic waste and the characterization of eco-enzymes based on them. This type of research is an experiment with a qualitative approach. The sample used is a mixture of kitchen organic waste, namely the production and characterization of eco-enzymes which include pH, COD, BOD, TSS, and TDS. The research results obtained data on eco-enzyme production by mixing 3 components in a ratio of 1 : 3: 10 (1 part sugar, 3 parts organic kitchen waste. 10 parts water), then put into a closed container and stored in a cool, dry place, circulation air is good, and dark for 3 months. Eco-enzyme characterization showed a pH of 2.59, a TDS of 2840mg/L, a TSS of 4.46mg/L, a BOD of 60 mg/L, and a COD of 13100mg/L. Kata kunci: Produksi, Karakterisasi, Eco-enzim